Implementing Digital Storytelling-based Tasks for the Teaching of Narrative Writing Skills - Hilwa Alfiani Fitri; Husnawadi Husnawadi; Ika Harianingsih (EDULANGUE, 2021)
Although the myriad study has been done for documenting the educational values of digital storytelling (DST) on EFL learners’ language mastery, the majority of the research does not depict students’ daily life tasks. To fill this void, this mixed-method research involving 24 EFL students explored the implementation of DST-based tasks for the teaching of narrative writing skills. Lied in TBLT methodology instruction of Anwar (2016) also task theory by Nunann (2004), this study aimed to examine the effect of DST-based task on students’ narrative writing skills and their perceptions about its implementation. The statistical evidence indicated a significant difference in the students writing scores for the pre-test score (M=53.54, SD=10.05) and students' narrative writing post-test (M=66.21, SD=12.56). Conditions where; t (23) - 6.545, p= 0.000. The qualitative finding also uncovered students' perceptions of digital storytelling-based task implementation; it found that digital storytelling-based tasks could promote students writing skills, their learning motivations, as well as their language development for several skills such as listening and their vocabulary enhancement. Implications and recommendations for future studies are discussed.